A Simple and Modular Access to 4-Mercapto-4-methylpentanoic Acid: A Useful Building Block in Antibody-Drug Conjugates Research - Salamone, Logan; Lepeintre, Martin; Revil-Baudard, Vincent L.; Serpier, Fabien; Petit, Laurent (Synthesis, 2023)
An efficient synthesis of 4-mercapto-4-methylpentanoic acid, a fragment notably found in Antibody-Drug Conjugates (ADCs), is reported using an intermolecular radical transfer reaction as the pivotal step. The reported approach displays several advantages over more traditional routes and is compatible with the chemistry involved in the construction of ADCs. Original analogues of the molecule of interest can be readily accessed using the method developed.
Keywords: ADC; xanthate chemistry; gaseous olefins; amide coupling; linker; Maytansinoids; mercapto acid